PENGARUH PENGGUNAAN APLIKASI KHOOT! DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PENDIDIKAN AGAMA KATOLIK PADA MATERI MARTABAT MANUSIA SEBAGAI CITRA ALLAH - Rosalina Oka; Hermania Bhoki; Yosep Belen Keban (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Learning the topic of Human Dignity as the Image of God (Imago Dei) in Catholic Religious Education requires meaningful learning experiences that encourage students' active participation so that conceptual understanding and value internalization can develop simultaneously. However, teacher-centered instructional practices often result in limited student engagement and low learning motivation. This study investigated the use of the Khoot! application as an interactive learning medium to enhance students' motivation and learning outcomes at SMP Negeri 1 Titehena. A quantitative approach was employed using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. Data were collected through achievement tests, learning motivation questionnaires, classroom observations, and documentation, and were analyzed using descriptive statistics and a paired-sample t-test. The findings revealed a substantial improvement in students' learning outcomes, with the mean score increasing from 60.12 on the pretest to 81.84 on the posttest. Students' learning motivation was also categorized as high, with a mean score of 84.41. Furthermore, the hypothesis test yielded a significance value of 0.002 (p < 0.05), indicating that the implementation of Khoot! had a statistically significant effect on both learning motivation and academic achievement. These findings suggest that integrating a game-based learning platform into Catholic Religious Education can create a more interactive and participatory learning environment while supporting students' deeper understanding and internalization of religious values. ABSTRAK Pembelajaran Pendidikan Agama Katolik pada materi Martabat Manusia sebagai Citra Allah memerlukan pengalaman belajar yang mampu mendorong keterlibatan peserta didik agar pemahaman konseptual dan penghayatan nilai dapat berkembang secara seimbang. Namun, proses pembelajaran yang masih didominasi metode konvensional sering kali berdampak pada rendahnya motivasi belajar dan terbatasnya partisipasi siswa. Penelitian ini mengeksplorasi pemanfaatan aplikasi Khoot! sebagai media pembelajaran interaktif untuk meningkatkan motivasi dan hasil belajar siswa di SMP Negeri 1 Titehena. Kajian dilakukan menggunakan pendekatan kuantitatif dengan rancangan Pre-Experimental Design model One Group Pretest–Posttest Design. Data diperoleh melalui tes hasil belajar, angket motivasi, observasi, dan dokumentasi, kemudian dianalisis menggunakan statistik deskriptif serta uji paired sample t-test. Hasil analisis memperlihatkan adanya peningkatan nilai rata-rata dari 60,12 pada pretest menjadi 81,84 pada posttest. Motivasi belajar siswa juga berada pada kategori tinggi dengan nilai rata-rata 84,41. Pengujian hipotesis menghasilkan nilai signifikansi sebesar 0,002 (<0,05), yang mengindikasikan bahwa penggunaan Khoot! memberikan pengaruh yang signifikan terhadap motivasi dan hasil belajar siswa. Temuan ini memperlihatkan bahwa integrasi media berbasis game-based learning berpotensi menciptakan pembelajaran Pendidikan Agama Katolik yang lebih partisipatif, interaktif, dan mendukung pemaknaan materi secara lebih mendalam.